On the Oedipal Rebellion of Todros Abulafia: An Intellectual Revisionist in Thirteenth-Century Spain - Ishay, Haviva (MiKAN, 2012)
Todros Abulafia has been identified by scholars as an unconventional poet in the Spanish school of Hebrew poetry. He engages in a ’secular’ dialogue with the Jewish religious tradition and in a ’modern’ one with the ancient Andalusi poetic tradition. For this reason, there exists an ongoing conflict in his poems between text and intertext. This article tries to analyze this conflict using Harold Bloom’s Anxiety of Influence. Through an analysis of Bloom’s six revisionary ratios in one of Abulafia’s qasidas, the article revisits Abulafia’s image as an epigone imitating the poems of his predecessors and recasts him as a ’strong’ poet endowed with an inertial force that enabled him to transform poetic influences into revisionist insights. Abulafia rewrites his precursors’ poems in an original way, and in so doing creates authentic poetry. Bloom’s model distinguishes him as an innovator and groundbreaker—an authentic son of thirteenth-century Spain.